(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores cybercrime as one of the most pressing phenomena of the modern digital era. It examines the key threats specific to the Republic of Uzbekistan, analyzes the underlying causes of their proliferation, and proposes measures to enhance the effectiveness of counter-strategies. Particular emphasis is placed on the role of the human factor and the imperative need to cultivate a resilient digital culture.